(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Low level of mathematical self-efficacy in students lessens their drive to study, which could culminate to poor mathematical outcomes. The objective of the paper was to figure out the level of mathematical self-efficacy among secondary level students. For this study quantitative paradigm was adopted, data were collected from the survey from 402 secondary school students of grade 9 to 12, randomly selected from two institutional and two community schools of Kathmandu. To measure the level of mathematics self-efficacy, the 14 items pertaining to mathematics self-efficacy were borrowed from MSEAQ prepared by May (2009). The alpha coefficient of the Self-efficacy scale was 0.91 and from the component matrix, each items have a factor loading greater than 0.4. A medium level of math self-efficacy but the lack of uniformity in mathematics self-efficacy was found. The mean mathematics self-efficacy score of male students was higher than female; the self-efficacy was slightly higher in institutional school than community school students. The mean self-efficacy score of grade 12 students was found highest and grade 9 was found least. The math self- efficacy was statistically significantly different based on gender and based on grade, but not based on types of school. The findings of this study indicate the need of stakeholders sustaining a support system that includes counselling, motivation, parental and teacher support, and other means to enhance students’ mathematics self- efficacy.